Preliminary results from the second flight of CREAM - MARROCCHESI, PIER SIMONE; H. S. AHN; P. ALLISON; BAGLIESI, MARIA GRAZIA; L. BARBIER; J. J. BEATTY; BIGONGIARI, GABRIELE; T. J. BRANDT; J. T. CHILDERS; N. B. CONKLIN; S. COUTU; M. A. DUVERNOIS; et al. (Advances in Space Research, 2008)
Launched from McMurdo (Antarctica) in December 2005, the balloon experiment CREAM (cosmic ray energetics and mass) collected about 15 million triggers during its second flight of 28 days. Redundant charge identification, by two pixelated silicon arrays and a time resolved pulse shaping technique from a scintillator system, allowed a clear signature of the primary nuclei. The energy was measured with a tungsten/SciFi calorimeter preceded by a graphite target. Preliminary results from the analysis of the data of the second flight are presented.